Histone deacetylase inhibitors sensitize lung cancer cells to hyperthermia: involvement of Ku70/SirT-1 in thermo-protection. - Mohamed K Hassan (Public Library of Science (PLoS), 2014)
This study describes the sensitization mechanism to thermal stress by histone deacetylase inhibitors (HDACIs) in lung cancer cells and shows that Ku70, based on its acetylation status, mediates the protection of lung cancer from hyperthermia (42.5°C, 1-6 hrs). Ku70 regulates apoptosis by sequestering pro-apoptotic Bax. However, its role in thermal stress is not fully understood. The findings showed that, pre-treating lung cancer cells with HDACIs, nicotinamide (NM) or Trichostatin A (TsA) or both significantly enhanced hyperthermia-induced Bax-dependent apoptosis in PC-10 cells. We found that hyperthermia induces SirT-1, Sirtuin, upregulation but not HDAC6 or SirT-3, therefore transfection with dominant negative SirT-1 (Y/H) also eliminated the protection and resulted in more cell death by hyperthermia, in H1299 cells through Bax activation. Hyperthermia alone primed lung cancer cells to apoptosis without prominent death. After hyperthermia Bax was upregulated, Bcl-2 was downregulated, the Bax/Bcl-2 ratio was inversed and Bax/Bcl-2 heterodimer was dissociated. Although hyperthermia did not affect total Ku70 expression level, it stimulated Ku70 deacetylation, which in turn could bind more Bax in the PC-10 cells. These findings suggest an escape mechanism from hyperthermia-induced Bax activation. To verify the role of Ku70 in this protection mechanism, Ku70 was silenced by siRNA. Ku70 silencing significantly sensitized the lung cancer cells to hyperthermia. The Ku70 KD cells underwent cytotoxic G1 arrest and caspase-dependant apoptosis when compared to scrambled transfectants which showed only G2/M cytostatic arrest in the cell lines investigated, suggesting an additional cell cycle-dependent, novel, role of Ku70 in protection from hyperthermia. Taken together, our data show a Ku70-dependent protection mechanism from hyperthermia. Targeting Ku70 and/or its acetylation during hyperthermia may represent a promising therapeutic approach for lung cancer.